AB0064 Progranulin Antibodies (PGRN-ABS) in Rheumatoid Arthritis More Frequent than in Psoriatic Arthritis. (10th June 2014) - Assmann, G.; Zinke, S.; Gerling, M.; Pfreundschuh, M.; Thurner, L.; Preuss, K.
Abstract : Background: Until recently, most research on progranulin (PGRN) had been foccussed on its role in neurodegenerative diseases as frontotemporal demetia. However, we discovered antibodies against PGRN in a protein array-based screening of plasma from various different rheumatic diseases (1, 2). Furthermore, PGRN-Abs have been proved to have neutralizing effect on PGRN plasma levels; PGRN itself showed antiinflammatory effects by its high-affinity to the TNFa receptor 1 and 2 causing a direct inhibition of the TNFa receptors. Objectives: To evaluate the prevalence of PGRN-Abs in sera of patients with rheumatoid arthritis compared to psoriatic arthritis patients and healthy controls Methods: PGRN-Abs were determined in sera of 201 patients of RA, 260 patients of PsA, and 97 healthy controls. The ELISA detecting PGRN-Abs were applied as previously described (2). The prevalence of PGRN-Abs in sera of RA were compared to PsA and healthy controls. Subgroup analyses has stratifyed the RA cohort according to gender, age, seropositivity of rheumatoid factor (RF) and ACPA, erosive course of disease, duration of disease, and the occurrence of anti-TNF treatment failure. The statistics was performed with the Mann-Whithney U test evaluating the differences between RA, PsA and healthy controls; the using the χ 2 test differences between the different RA subgroups were investigated. A p-value of <0.5 was considered significant. Results: PGRN-Abs was detected in 32.6% of the RA cohort with significant higher prevalence compared to PsA (19.2, p=0.014) and healthy controls (1.03, p=0.001). Among the RA subgroups patients on age elder than 60 years (versus younger than 60) and patients with disease duration longer than 5 years (versus shorter than 5 years) showed significantly more frequent PGRN-Abs in their sera. Conclusions: Here we present the first study evaluating the PGRN-Abs in sera of patients with RA. Longer duration of disease seems to favor the occurrence of PGRN-Abs. PGRN-Abs could been detected significantly more frequent in RA than in PsA. References: Thurner L & Pfreundschuh M et al, PGRN in autoimmune diseases, J Autoimmunity, 2012 Thurner L & Assmann G et al, PGRN in PsA, Arth Res Th, 2013 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5925